Pancreas Protective Effects of Telang Flower Extract (Clitoria ternatea L.) Against induced Male White Rats (Rattus norvegicus) Aloksan - Edi Kamal, Sainal; Rusli, Rusli; Fani Temarwut, Farid; Biana Sary, Skolastika (Politeknik Sandi Karsa, 2022)
Studies have been conducted on the protective effects of pancreatic telang flower extract (Clitoria ternatea L.) against white rats (Rattus norvegicus) induced by alloxane-induced by laboratory experiential methods. Thegoal is to determine the protective effect of pancreatic telang flower extract (Clitoria ternatea L.) against white rats (Rattus norvegicus) induced by alloxane which has the potential to be anti-diabetic. The mice used were 15 heads, the mice were divided into 5 groups. Each group consisted of 3 mice. Three groups were given a suspension of Telang Flower Extract at a dose of 150 mg/kgBB, 300 mg/kgBB, 450 mg/kgBB, and 1 group as a negative control was given a 1% Na-CMC suspension w/v. The administration of telang flower extract was carried out for 5 days and induced by aloksan of 150 mg / KgBB for 2 days. Blood draws are carried out 3 times, namely on the first day, day 6, and day 8 and then measurements of glucose and albumin levels are carried out. Based on the research that has been carried out, it can be concluded that the administration of telang flower extract (Clitoria ternatea L.) at a dose of 150 mg/KgBB,300 mg/KgBB, and 450 mg / KgBB have a protective effect not significantly different.